THE ROLE OF GREEN ACCOUNTING IN ACHIEVING CORPORATE SUSTAINABILITY IN DEVELOPING COUNTRIES; GREEN ACCOUNTING PRACTICE IN BANGLADESH - DUTTA, TAPASH KUMAR; ADALETEY, JENNIFER ELLAH; RAJU, VALLIAPPAN; PHUNG, SIEW POH (International Journal of Psychosocial Rehabilitation, 2020)
This paper highlighted the importance of green accounting concepts, roles, practice, application and improvement to corporate identity and sustainability of companies in developing economies such as Bangladesh. The study revealed how green accounting improves environmental performance, control cost, and invest in safe technologies that help in decisions such as product mix, product retention, and product pricing. This study also highlighted the environmental, social and economic impact of business by incorporating both economic and environmental information in business decisions. This study adopted a questionnaire for data collection and the respondents were selected at random. The study also suggested design and emphasis of industry specific accounting framework in terms of green accounting, corporate sustainability and disclosures in order to achieve maximum implementation and practice. This study is limited to selected Malaysian and Bangladeshi companies that included private sector, public sector, multinational companies, and entrepreneurs operating Dhaka, Narayanganj and Chittagong . This study adopted Kuala Lumpur as benchmark for information, which were collected to improve organizational performance with objective of maintaining proper environmental stands required to achieve corporate sustainability. The findings may not be applicable to countries with economic and industrial policies different from those considered in this study.